CRYPTOPHTHALMOS - Puji Indah Lestari (Universitas Fort De Kock, 2021)
Introduction : Cryptophthalmos (hidden eye) is a very rare disease. In these patients there is a failure of differentiation of the eyelid structures so that there is continuous skin from the forehead through the eyes to the cheeks and the undercoat fuses with the cornea, usually accompanied by a malformation of the eyeball. This disorder is suspected to be caused by mutations in the FRAS 1 gene, a gene that involves skin epithelial morphogenesis during early embryonic development. Based on the degree of severity, Cryptophthalmos is grouped into three namely complete Cryptophthalmos, partial Cryptophthalmos and abortive Cryptophthalmos.Method: A case report of a baby girl after 4 days with her left eye not opening since birth. There was no abnormality in the right eye. The patient is the second child of two siblings with siblings, there is no abnormality in both eyes. In the left eye, the palpebral skin grew together from the forehead to the cheek, the palpebral fissure could not be identified. No eyelashes and eyebrows.Result: The patient is referred to the pediatrics department to see if this disorder is isolated or accompanied by Fraser's syndrome. Consul from the pediatrics department did not find any other congenital abnormalities.Conclusion: Cryptophthalmos is a congenital disorder that can occur isolated or accompany other syndromes. Cryptophthalmos usually occurs with ocular deformity so that the visual prognosis is not good.Keywords: Cryptophthalmos, congenital abnormalities, Fraser's syndrome.Pendahuluan : Cryptophthalmos ( Mata yang tersembunyi ) merupakan suatu penyakit yang sangat jarang terjadi. Pada pasien ini terdapat kegagalan diferensiasi dari struktur kelopak mata sehingga terdapat kulit yang berkesinambungan dari dahi melewati mata hingga pipi dan lapisan bawahnya menyatu dengan kornea, biasanya disertai dengan malformasi bola mata. Kelainan ini dicurigai terjadi akibat mutasi gen FRAS 1, yaitu suatu gen yang melibatkan marfogenesis epitelial kulit selama awal perkembangan embrio. Berdasarkan derajat keparahannya, Cryptophthalmos dikelompokkan atas tiga yaitu Cryptophthalmos komplit, Cryptophthalmos parsial dan Cryptophthalmos abortif.Metode: Laporan kasus seorang bayi perempuan usai 4 hari dengan mata kiri tidak membuka sejak lahir. Mata kanan tampak tidak ada kelainan. Pasien anak kedua dari dua bersaudara dengan saudara kandung tidak ada kelaianan pada kedua matanya. Pada mata kiri tampak kulit palpebra yang tumbuh menyatu dari dahi hingga pipi, fisura palpebra tidak bisa diidentifikasi. Bulu mata dan alis tidak ada. Hasil: Pasien dikonsulkan ke bagian anak untuk melihat apakah kelainan ini terisolasi atau disertai dengan sindrom Fraser. Konsul dari bagian anak tidak ditemukan kelainan kongenital lainnya.Kesimpulan: Cryptophthalmos merupakan kelainan kongenital yang dapat terjadi terisolasi ataupun menyertai sindroma lainnya. Cryptophthalmos biasanya terjadi disertai deformitas okular sehingga prognosa visusnya tidak baik.Kata Kunci: Cryptophthalmos, kelainan kongenital, sindroma Fraser.